The common error of common sense: An essential rectification of the accounting approach - Egmont Kakarot-Handtke (Levy Economics Institute of Bard College, 2012)
This paper takes the explanatory superiority of the integrated monetary approach for granted. It will be demonstrated that the accounting approach could do even better, provided it frees itself from theoretically ill-founded notions like GDP and other artifacts of the equilibrium approach. National accounting as such does not provide a model of the economy but is, rather, the numerical reflex of the underlying theory. It is this theory that will be scrutinized, rectified, and ultimately replaced in what follows. The formal point of reference is the integrated approach to credit, money, income, production and wealth of Wynne Godley and Marc Lavoie.
Keywords: B41; E01; 330; New Framework of Concepts; Structure-Centric; Axiom Set; Primacy of Theory; Income; Profit; Distributed Profit; Money; Flow; Residual; Transaction Matrix; General Complementarity